Integrating AI with constructivist pedagogy for science education in marginalized regions: A systematic review - Manik, Manganju; Rahmi, Ulfia (STAI Auliaurrasyidin Tembilahan, 2026)
Enhancing 21st-century competencies in frontier, remote, and disadvantaged (3T) regions remains challenging due to limited infrastructure, restricted digital access, and the need for culturally relevant science learning. This study employs a systematic literature review of selected peer-reviewed studies published between 2011 and 2025 to examine how constructivist-based science learning integrated with digital technology and artificial intelligence (AI) can support equitable education in low-resource contexts. The findings indicate that effective technology-enhanced learning in 3T regions is pedagogy-driven rather than technology-driven, grounded in the integration of constructivism, progressivism, and social reconstructionism. AI, learning management systems, and interactive digital media can support personalized learning, formative assessment, and the development of scientific literacy, numeracy, and digital literacy when embedded within adaptive instructional frameworks. However, the literature also reveals significant feasibility constraints related to digital access, teacher readiness, and ethical considerations. Therefore, context-aware, low-bandwidth, and teacher-mediated digital solutions are essential to ensure equitable and sustainable science learning in 3T regions.